Retinal Re-detachment after Silicone Oil Removal - Tahseen Mahjoo, Kashif Manan, Ata-ur-Rasool, Nasir Chaudhry, Asad Aslam Khan (Pakistan Journal of Ophthalmology, 2017)
Removal of silicone oil is a procedure that have a risk of re-detachment of the retina due to reproliferation of epiretinal membranes and causing traction on the retina .The recurrence of retinal detachment has been reported to occur in 20-40% of cases. Redetachment of the retina is not dependent on the duration of silicone oil in the eye and similarly the technique used for its removal. Objectives: The objectives of this study were to see the recurrence rate and the time interval of retinal re-detachment after (ROSO) removal of silicone oil. Study Design: Quasi experimental study design was used Place and duration of study: This study was conducted at ophthalmology department unit-3 Mayo Hospital Lahore and duration was 6 months from 1st.October 2016 to 31 March 2017. Material and Methods: Total fifty (50) patients that underwent 3-ports PPV± scleral buckle with SO (Silicone oil) used as an internal tamponade of either sex were included in this study. All the subjects were selected by a convenience type of non-probability purposive sampling. Results: Out of a total of 50 patients, 15 (30%) developed retinal re-detachment, which was within the first 3 months after ROSO. Out of 35 patients with attached retina after silicone oil removal 13(37%) had improvement in Snellen visual acuity of one line or more whereas 22(63%) had no improvement in their vision. We observed that the silicone oil duration as an endotamponade had no major differences on the recurrence rate of retinal detachment after its removal. Conclusion: Recurrence of retinal detachment after (ROSO)removal of silicone oil is common which in this study more than half of re-detachments occurred in the first month of silicone oil removal. The visual acuity improved in only13 (37%) patients after silicone oil removal with attached retina. Keys words):- (PPV) pars plana vitrectomy, (ROSO) removal of silicone oil